RESEARCH METHODS FOR THE DEVELOPMENT OF DA'WAH THEORY - Siti Nurfadilah; Imam Bonjol Jauhari (Indonesian Journal of Islamic Communication, 2022)
Da'wah as a science that has a number of research fields, was actually recently born and formulated. Whereas da'wah as an activity and instrument of spreading Islam has been known for a long time. Awareness of the need for an independent science that has its own space and method regarding da'wah and its ins and outs, led to the birth of a da'wah scientific discipline. The method in writing this article the author uses a literature review. Where the references used are reading books as well as other journal articles related to the analysis of possibilities in the use of research methods in the study of da'wah. The results of the author's analysis according to the readings are that da'wah research can use two methods, namely qualitative research methods and quantitative research methods with three approaches: empirical, philosophical and normative approaches. Qualitative research can be done with a descriptive approach, an ethnographic approach, a historical approach, case research and field research, and content analysis. While Quantitative Research can use populations and samples such as Correlation, Experimental-Real, Quasi-Experimental Research, Action Research and Content Analysis Research.